Remediation and management of low vision - Cole, Roy Gordon; Rosenthal, Bruce P; London, Richard (Mosby, 1996)
State University of New York, New York City.
Mosby's optometric problem-solving series
Keywords: optometrie; Optometry; poruchy zraku; Vision Disorders; oftalmologie